1994
DOI: 10.1002/bjs.1800810911
|View full text |Cite
|
Sign up to set email alerts
|

Light-reflective cerebral oximetry and jugular bulb venous oxygen saturation during carotid endarterectomy

Abstract: A novel instrument using reflected near-infra-red light spectroscopy to measure cerebral oxygen saturation non-invasively was evaluated during carotid endarterectomy; cerebral perfusion was compared with jugular bulb venous oxygen saturation and transcranial Doppler ultrasonographic measurements. Initially, oximetry sensors with light source-detector separation distances of 10 and 27 mm were positioned over the frontal area, while a cannula positioned in the jugular bulb permitted sampling for jugular bulb ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 8 publications
0
30
0
Order By: Relevance
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, normal TOI values have been reported to range from 65% to 85%. 14,36 -41 Although a number of authors have compared NIRS with other techniques such as jugular bulb oxygen saturation (SjO 2 ), transcranial Doppler ultrasonography and somatosensory-evoked potential 15,37,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] or with neurologic events, few have attempted to define an absolute threshold for ischemia. 13,14,16,17,46,[57][58][59] Most studies of this type using NIRS make no attempt to correct for extracranial contributions to signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies failed to demonstrate the clinical usefulness of the cerebral oximeter INVOS 3100A in carotid surgery. One reason was the use of reference methods, such as jugularvenous oximetry, 10 that are well recognized as unreliable for detection of focal ischemia. 17 Furthermore, because of the limited number of patients studied, comparison of the NIRS results with individual neurological outcome did not provide conclusive evidence for the usefulness of this device.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provided evidence that changes in cerebral oxygenation caused by cross-clamping of the ICA can be monitored by means of near-infrared spectroscopy (NIRS). [7][8][9][10] Since no "gold standard" with which to test the sensitivity and specificity of cerebral oximetry exists, the results of NIRS need to be compared with other validated forms of neuromonitoring. 11 A loss of cortical SEP is a good indicator of cerebral hypoperfusion and is able to identify patients at risk for intraoperative stroke.…”
mentioning
confidence: 99%
“…Data from previous studies demonstrated that absolute numbers of regional SO 2 are of little value in interpreting results obtained by semiquantitative NIRS. 6,8,26,28,32,40,41 Recently, Q-NIRS measurements were introduced, which enabled accurate quantification of brain tissue oxygenation. Quantitative frequency-domain NIRS has two major advantages compared with CW-NIRS: it provides quantitative values of hemoglobin concentrations (HbO 2 , HHb, tHb), and it directly monitors brain tissue oxygenation independently from oxygenation of the skin and scalp.…”
Section: Role Of Nirsmentioning
confidence: 99%